Analisis Performansi Sistem Pembangkit Listrik Tenaga Air Jenis Turbin Pelton Dengan Variasi Bukaan Katup Dan Beban Lampu Menggunakan Inverter - Irawan, Hery; Syamsuri, Syamsuri; Rahmad Q, Rahmad Q (JHP17 (Jurnal Hasil Penelitian), 2018)
Energy crisis engulfing the world recently has become people’s concern in finding new energy sources which are cheaper and available in the large numbers. The alternative is energy source to drive a turbine. In this case, water will gradually change its potential energy to be kinetic energy which then becomes mechanic energy to move turbine shaft. In this way, the yielded power source can drive other tools needed such as generator which produces electric current. The turbine used in the research was pelton turbine with inverter. The comparison of various lamp power i.e.3,5,9, and 12 watts was analyzed. The data collection was conducted on variables of water capacity, voltage, electric curent, electric power, and hydraulic power. The highest electric power 1.761 watts happened on the lamp power 9 watts and valve opening 900 . This lamp had maximum values of capacity (Q) 1.565x10-3 m3 /s, voltage 0,2 V, electric current 7,87 A, electric power 1.761 watt, and hydraulic power 7.571 watts. Keywords: pelton turbine, valve-opening, dynamo, nozzle, turbine spin, inverter.